G461(P) If the KAP fits – knowledge, attitude and practice towards neonatal health in rural Cambodia. (25th October 2020) - Parkhill, E; Patel, K; Leng, D; Vanna, D; Prak, M; Watson, G; Riedel, A; Turner, C
Abstract : Introduction: Cambodia has one of the highest neonatal mortality rates (NMR) in Southeast Asia: 18 per 1, 000 births. Most neonates die in rural areas, often in the community, and before reaching a health facility. Community Health Workers (CHWs) constitute a vital part of the national health system, providing health education and advice to their village. This reported study is a component of the five year 'Saving Babies' Lives' (SBL) programme, which aims to reduce NMR by implementing a comprehensive neonatal healthcare package in a rural Cambodian province. The programme intervention is participant action research to empower CHWs. The programme required a situation analysis of baseline CHW knowledge, attitude and practices, and to monitor temporal change; no SBL intervention had occurred during the timeframe examined. Aim: To examine the results and application of a neonatal Knowledge Attitudes and Practice (KAP) survey, for CHWs in a rural province in Cambodia, between 2018 and 2019. Methods: A bespoke neonatal CHW assessment tool, using a KAP survey method and based on national guidelines, was developed into a tablet-based survey using KoBoToolbox. The KAP survey comprised 47 grouped knowledge yes/no/unsure questions, and seven attitude and six practice questions using a 5-point Likert scale. In August 2018 and July 2019 all CHWs attending existing monthly meetings were surveyed. Results: 420 CHWs were surveyed in 2018 and 375 in 2019. 87% of knowledge questions were correctly answered in 2018, and 88% in 2019. Mean attitude scores were similar in 2018 and 2019 (3.95 and 3.87 respectively).Mean practice scores were also similar (2018: 4.46; 2019: 4.30). Limitations in interpreting results include CHWs conferring during survey completion, and some confusingly worded questions. Conclusion: High baseline KAP scores possibly reflect the high volume of NGO-led CHW education in Cambodia. High scores mean change over time is unlikely to be captured, so an annual CHW KAP survey will be discontinued for the SBL programme. KAP surveys are a useful tool for situation analysis and to measure temporal changes. This study shows that the use of the KAP survey needs to be assessed and its use adapted according to findings.